Frequency of Urinary Tract Infection in Patients with Indwelling Catheters - Mir, Ifrah Amjad; Muhammad Arslan (Indus Journal of Bioscience Research, 2025)
Objective: “To determine the frequency of urinary tract infection in patients with indwelling catheters”. Study design: Cross Sectional study. Study place and duration: Department of Medicine, Shaukat Khanum Memorial Cancer Hospital & Research Center Lahore from 24-1-2024 to 24-5-2024. Methodology: Patients were included from medical wards. Demographic details, medical history duration of hospital admission, were also noted. Then fresh urine sample was taken for culture examination. Reports were obtained and if bacterium detected, then urinary tract infection was labeled. All the data was recorded in a Performa and analysed in SPSS. Results: The mean age of patients was 51.20 ± 12.45 years. There were 73 (58.4%) males and 52 (41.6%) females. Urinary tract infection was positive in 95 (76%) patients who were admitted in hospital and received indwelling catheterization. The most common pathogen detected in urine samples was Escherichia coli [56 (44.8%)], followed by Pseudomonas aeruginosa [18 (14.4%)], Klebsiella pneumonia [12 (9.6%)], Enterococcus species [11 (8.8%)], Candida albicans [9 (7.2%)], Candida tropicalis [8 (6.4%)], Trichosporon asahii [5 (4.0%)], Staphylococcus aureus [4 (3.2%)]. Conclusion: Thus, the chances of Urinary tract infection in hospital admitted patients are high who received indwelling catheterization.